Performance-Messung ohne Rückgriff auf kapitalmarkttheoretische Renditeerwartungsmodelle - Carsten Wittrock; Manfred Steiner (Kredit und Kapital, 1995)
Performance-Messung ohne Rückgriff auf kapitalmarkttheoretische Renditeerwartungsmodelle – Eine Analyse des Anlageerfolges deutscher Aktieninvestmentfonds In diesem Beitrag wird die Performance von 21 deutschen Aktieninvestmentfonds in der Zeit von 1974 – 1991 unter Verwendung ihrer Renditezeitreihen als alleiniger Informationsquelle analysiert. Unter anderem wird dabei die von Grinblatt/ Titman entwickelte Positive Period Weighting Measure eingesetzt. Auf deren Überlegungen zurückgreifend, wird gezeigt, daß ein expliziter Zusammenhang zwischen der Performance-Messung und einer Theorie der Wertpapierbewertung nicht erforderlich ist. Eine korrekte Zuweisung von Performance wird durch ein relativ uw/o-effizientes Portfolio, welches lediglich Wertpapiere enthält, die aus der Sicht des Investors als handelbar angesehen werden, ermöglicht. Die Ergebnisse bei der Anwendung dieses auch Timingfähigkeiten berücksichtigenden – – Performance-Measurement without Links to Particular Equilibrium Models – An Analysis of the Performance of German Mutual Funds Using only returns as a source of information we examine the performance of 21 German mutual funds between 1974 – 1991. The measures employed include the positive period weighting measure proposed by Grinblatt/Titman. Based on their insights it is shown that links between performance measures and particular equilibrium models are not necessary and that an unconditional mean-variance efficient portfolio of assets that are considered tradable by the evaluated investor provides correct inferences about an investor's performance. The results from applying that measure which overcomes timing-related estimation problems were almost identical to the results obtained by employing the Jensen-measure. Our findings were supported by applying stochastic dominance criteria which utilize the entire probability density function of returns rather than a finite number of moments such as mean and variance. We found no evidence that the funds on average provide investors with superior performance that surpasses of a broad performance equity index over the sample periods.
Keywords: 330